Detoxification of Peptide-Containing Biotoxins - Ilya V. Lyagin; Olga V. Maslova; Olga V. Senko; Nikolay A. Stepanov; Elena N. Efremenko (Вестник войск РХБ защиты, 2024)
Highlights. Peptide biotoxins are important problem for human health and as lethal agents due to their wild diversity of chemical structures and biological sources.Such peptide biotoxins and prion proteins can be effectively neutralized by different methods, including by protease treatment.Relevance – biological toxins containing peptides possess serious danger for life and well being of humans. There are a lot of reviews summarizing immunologic protective measures against these toxins. As opposed to that an enzymatic detoxification of biotoxins is, at best, considered superficially.The purpose of the work is analysis of the main up-to-date trends of development of protective remedies against biotoxins of peptide nature.The source base of the research is mainly English–language scientific literature available via the global Internet network, as well as the authors' own published experimental studies.The research method is analytical.Results. Currently the efficiency of detoxifying immunological drugs is surging due to highly productive methods of screening and selection of effective clones producing monoclonal antibodies. Special attention in the review is paid to application of hydrolytic enzymes which are considered in the work as alternative for immunobiological agents during detoxication of peptide biotoxins. The natural analogue of detoxifying enzymes is a system “toxin–antitoxin” of procaryotes. More than four types of inhibitors of biotoxins are know: blocking of their catalytic activity; hindering of their target receptors; inhibiting of toxin by acting on its structure; and allosterically modulating of biotoxin activity. There are encouraging data on application of detoxifying enzymes for neutralization of prions in soils and for treatment of prion complication.Conclusions. Application of proteases for detoxification of peptide biotoxins and prion peptides could be considered as viable alternative to detoxifying immunobiological agents.